State distribution of medical universities graduates as a form of eliminating staff shortages in the healthcare sector - S. Ye. Titor (Вестник университета)
The issue of staff shortage in socially important sectors of Russian economy, including health care, is not new. The state adopts various mechanisms and implements projects aimed at its solution, but the efforts are insufficient. The statistics of the need for personnel in the health care sector has been analyzed as a justification for the relevance of the study. The experience of the Soviet distribution of graduates, foreign experience, and new draft laws have been studied, and proposals for updating the “old” experience considering the new realities have been formulated. The updated mechanism of the medical graduates state distribution has been proposed. Theoretical conclusions about the necessity of introducing the socially important specialties concept into the law enforcement turnover have been formulated, and the author’s definition has been given. The comparative analysis of the existing mechanisms of providing the labor market with qualified specialists (target training) with the proposed order of distribution has been carried out, and the advantages of the latter and the disadvantages of the existing one have been shown. Proposals for updating the current legislation necessary for state distribution implementation in socially important areas of training, such as health care, have been formulated. The proposed system will allow solving another important problem such as youth employment.